KESADARAN HALAL TRACEABILITY PADA INDUSTRI KULINER TRADISIONAL: ANALISIS PERSEPSI PEDAGANG KAKI LIMA DI DESA SAMBONGDUKUH PASCA KEWAJIBAN SERTIFIKASI HALAL - Wahyu Styabudi (Jurnal Ilmiah Ekonomi Syariah, 2026)
AbstractHalal certification has become an important issue for food and beverage business actors in Indonesia, especially after the implementation of mandatory halal certification under the Halal Product Assurance regulation. However, the discussion on halal certification is often focused on formal businesses, while traditional culinary traders and street vendors still face practical limitations in understanding halal traceability. This article aims to analyze the awareness of halal traceability among street food vendors in Desa Sambongdukuh, Kecamatan Jombang, Kabupaten Jombang. This study uses a qualitative descriptive approach through literature review, regulatory analysis, and a proposed field-based interview framework for street vendors. The findings show that halal awareness among traditional culinary traders tends to be understood mainly as the use of permissible ingredients, while traceability is not yet fully understood as documentation of raw materials, suppliers, processing tools, storage, and serving practices. The main challenges include limited knowledge of certification procedures, lack of written records, cost perception, digital literacy barriers, and dependence on informal supply chains. This article argues that halal traceability for street vendors should be developed through simple documentation, local assistance, and gradual education. Keywords : halal traceability, halal certification, street vendors, traditional culinary industry, micro enterprises, Desa Sambongdukuh